Analysis of policies for use of medically important antibiotics in animals in Namibia: implications for antimicrobial stewardship. Issue 10 (3rd October 2022) - Kaupitwa, Coleen Jennifer; Nowaseb, Seth; Godman, Brian; Kibuule, Dan
ABSTRACT: Background: In Namibia, overuse of medically important antibiotics in animals is common and is a considerable driver of antimicrobial resistance. The study aims to analyze policies, resistance patterns, and consumption of these antibiotics used in animals in Namibia. Research design and methods: A scoping review and retrospective descriptive analysis of policies, resistance patterns, and use of these antibiotics in Namibia was conducted, and assessed against the Access, Watch and Reserve (AWaRe) antimicrobial use guidance. Results: Of the forty-five antibiotic products registered for use in animals, 77.8% are Access antibiotics, 68.9% are broad-spectrum and 60% are over-the-counter antibiotics – mainly tetracyclines, penicillins and sulfonamides. There is misalignment of antibiotic use policies for animals and humans and currently no guideline for antibiotic use in animals. Most medically important antibiotics are indicated for control of gastrointestinal (77.7%), musculoskeletal (71.1%), and respiratory (46.7%) infections, and for growth promotion (4.4%). There is high resistance to AWaRe Access antibiotics- sulfonamides (19.5–100%), tetracyclines (56–100%), and penicillin (13.5–100%). Conclusion: Whilst Namibia banned the use of antibiotics in farming, current policy frameworks are inconsistent across sectors, and promote overuse of broad-spectrum important antibiotics in animals. A multi-sectoral one health approach is required to harmonize antibiotic use policies and reduce resistance.